FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN MODAL INTELEKTUAL - Andani Parameswari, 12.05.52.0223; Indarti, MG. Kentris (Students' Journal of Accounting and Banking, 2017)
This study aims to analyze the effect of profitability, company age, firm size, leverage and growth on intellectual capital disclosure on manufacturing companies listed on the Stock Exchange in the period 2012-2015. In this study the researchers used the entire manufacturing population listed on the BEI in the period 2012-2015. The method used is purposive sampling method. The test equipment in this study used multiple linear regression. The result of this research is profitability have positive effect on intellectual capital disclosure. While the age of the company, firm size, leverage and growth does not affect the disclosure of intellectual capital.Keywords: Profitability, Company Age, Firm Size, Leverage, Growth, Intellectual Capital Disclosure